Analysis Of Life Forms And Vertical Regions Of Poaceae Family In The Flora Of The Kuhitang Ridge - A.J. Ibragimov; M.A. Abdimuminova (Zien Journals, 2021)
The flora of the Kuhitang ridge includes 59 species belonging to 37 genera of the Poaceae family. In the Kuhitang ridge, members of the Poaceae family are divided into three vertical regions. The diversity of the main species in the family coincided with the mountainous region. This is a characteristic feature of the flora of Central Asia. The Adir region is rich in both quantity and quality. The number of species in the pastures is relatively small, but the diversity is satisfactory.
Keywords: Poaceae; family; flora; mountain